THE IDEA OF RADICAL FEMINISM IN THE NOVEL “WOMAN AT POINT ZERO” - Az-Zahra, Andi Nurfatimah; Mustikawati, Yunitari (Journal of English Literature and Linguistic Studies, 2024)
This research aims to the form of radical feminism and how it is resisted in the novel "Woman at Point Zero". To obtain the data for this analysis, the researchers used a descriptive qualitative method. The researchers reads the novel entitled "Woman At Point Zero" 4 times. This novel tells about a life journey of a girl named Firdaus who is a woman from Egypt who has lived in a village since childhood but she was employed as a commercial sex worker after adulthood. There are 7 types of feminism but the most prominent type in this novel is radical feminism with libetarian radical feminism and cultural radical feminism having 10 extracts, self actualization 3 extracts, dare to act 7 extracts, and the power of speak up 3 extracts. The resistance to the freedom of feminism is that Firdaus speaks up, apart from the resistance of speaking up, Firdaus also dares to act and self-actualize.